(untitled) (Journal of the College of Basic Education, 2025)
This research aims to study the implicit connotations of the declarative and performative styles in the poem “Rain Song” by Badr Shakir al-Sayyab, through employing a modern linguistic approach that is evident in Paul Grice’s theory of dialogical implicature. The research analyzed the declarative and performative styles with the aim of revealing their implicit connotations according to the theory of dialogical implicature. The research addressed the meanings implied dialogically, while identifying the Gricean principle that was violated. The importance of the research lies in the fact that it deals with the poem “Rain Song,” which has profound connotations. Through the linguistic methods he used, the poet was able to move from its original connotations to dialogue-related purposes that can only be achieved by someone who is familiar with the context and the situation in which it was said. The research has reached multiple results, the most prominent of which are the following: First: The context plays an important and decisive role in determining the meaning required by the dialogue. Without linking the article to the situation and resorting to clues, the meaning would be open to many worlds, but the context is what defines them and directs them to a specific meaning. Second: Among the metaphorical meanings that the declarative style in his poem reached are: expressing the suffering of the naked and hungry, threat and warning, sorrow, waiting and hope. As for the performative styles such as the question, it reached meanings required by the dialogue, including: sorrow and regret, which are two indirect meanings required by the dialogue, and they came in harmony with the situation and context. The call was intended to express astonishment, and it is an indirect meaning that requires dialogue. As for the imperative style, we did not find it in the poem “Rain Anthem” in a direct way and in its standard forms, but rather we understood it implicitly through structures from which the indirect speech act is understood, represented by the imperative verb that the poet presented in an innovative artistic way by linking it to images and symbols to arouse feelings and engage the mind of the recipient. Most of the indirect imperative verbs revolved around rain, life and hope. As for the imperative style, we did not find it in the poet’s poem in a direct and explicit way, but the poet employed extensively what is called the metaphorical or implicit prohibition. In his poem, the poet blames, reproaches and rebukes the rain or the events that it symbolizes.